Primary Submandibular Tuberculosis: An Unusual Cause of Submandibular Salivary Gland Enlargement - Dadwal, Madhuri (Springer-Verlag, 2011)
A case report of very rare Primary Tuberculosis of Submandibular Gland. This is presented in view of its rarity and highlighting the importance of histopathological examination and Polymerase chain reaction (PCR) to reach the final and exact diagnosis of disease.